Continuous Subcutaneous Use of Levetiracetam: A Retrospective Review of Tolerability and Clinical Effects. (1st December 2014) - Rémi, Constanze; Lorenzl, Stefan; Vyhnalek, Birgit; Rastorfer, Karin; Feddersen, Berend
ABSTRACT To evaluate the tolerability and clinical effects of subcutaneous (SC) levetiracetam for the treatment of epileptic seizures in a palliative care setting, we conducted a retrospective chart review of patients treated with subcutaneous levetiracetam in the Department of Palliative Medicine at the University Munich, between September 2006 and March 2013. The following parameters were extracted from the charts: reason for antiepileptic drug treatment, daily dose, concentration, infusion rate, co-administration of other drugs, and clinical effects. Furthermore, the charts were screened for signs of adverse drug reactions, e.g., irritation or pain at the infusion site. We identified 20 patients that were treated with levetiracetam SC in the inpatient (n = 7) and outpatient (n = 13) settings. Most patients (n = 17) tolerated the subcutaneous infusion well. Nineteen patients (95%) received levetiracetam in combination with other drugs. These were mainly metamizol (80%), midazolam (75%), and morphine (45%). The median dose of levetiracetam was 95.8 mg/h (SD 37 mg/h), median osmolarity of the infusion solution 2203 mOsmol/L (SD 717 mOsmol/L), and infusion rate 2 mL/h (SD 2.4 ml/h). In 16 patients (80%), seizures were controlled and status epilepticus were interrupted, respectively. We conclude that SC levetiracetam is an effective treatment and well tolerated in the palliative care setting.